The construction of hydro-social conflicts and the water-power relationship in two hydroelectric projects in Guerrero, Mexico - TERCERO-CRUZ, Laura (Utopía y Praxis Latinoamericana, 2023)
In this paper, we do a review of two case studies that shows the continuity in the construction of hydro-social conflicts that were triggered by the promotion of hydroelectric dam projects as generators of development in Mexico. Without prior consultation processes, socio-environmental impact studies and with the presence of water-power discourses, they affected several indigenous communities in the Northern, Central and Costa Chica regions of Guerrero. Through a table of analysis, the categories used in the review of these cases such as: scale, region, community organizations, civil society, state authorities, the private sector and the methodologies used in the reviewed studies are shown. All this in order to highlight these iconic cases of the State of Guerrero at the end of the 20th century and the beginning of the 21st century as hydro-social conflicts where the water-power relationship was present and were antecedents of other later socio-environmental conflicts in this state.